Effect of Product Promotion, Quality Products, Consumer Satisfaction in Forming Consumer Loyality to Return Buying Safety Shoes Products CV. Berkah Karya Jaya - Muhandisuddin, Muhammad Noor (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2019)
CV. Berkah Karya Jaya is a company engaged in the production of safety shoes that have sold products in various provinces in Indonesia. In the last few months CV. Berkah Karya Jaya decreased sales turnover caused by marketing strategy factor, product quality and customer satisfaction factor. Customers in the purchase is influenced by several factors, among others, the cheap price, product quality and suitability between price and quality obtained which will affect the satisfaction of customers when using the product. Therefore the purpose of this research is the influence of promotion strategy, product quality and satisfaction to customer loyalty. The population in this study are all customers of safety shoes from CV. Berkah Karya Jaya. The sampling technique used is purposive sampling where the researcher determines the customer sample recorded in the CV. Berkah Karya Jaya based on the criteria that have been determined at least in the last year that is the number of 100 people. The result of the research found that marketing strategy, quality and product satisfaction have significant effect either partially or simultaneously to customer loyalty CV. Berkah Karya Jaya. Product Promotion variables have a greater influence on customer loyalty than other variables that show regression coefficient value of 0.231 while the regression coefficient variable product quality and satisfaction each of 0.156 and 0.133. Keywords: product promotion, quality products, cunsomer satisfaction and cunsomer loyality